2018
DOI: 10.3389/fpsyg.2018.01973
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Individual Variability Across Fluid Cognition Can Reveal Qualitatively Different Cognitive Styles of the Aging Brain

Abstract: Dispersion is a measure of intra-individual variability reflecting how much performance across distinct cognitive functions varies within an individual. In cognitive aging studies, results are inconsistent: some studies report an increase in dispersion with increasing age and decline in performance, while others report an increasingly homogenous cognitive profile in older adults. We propose that inconsistencies may reflect qualitative differences in the cognitive functioning of the aging brain: age-groups may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 92 publications
2
20
0
Order By: Relevance
“…Yet, dispersion scores emerged as associated with increasing age and fewer years of formal education, in keeping with previous studies [14,20,41].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Yet, dispersion scores emerged as associated with increasing age and fewer years of formal education, in keeping with previous studies [14,20,41].…”
Section: Discussionsupporting
confidence: 88%
“…Our work takes some steps to address this. From a selection of established risk factors for AD, we found that cognitive dispersion increased with age -findings that resonate with comparisons between age-groups [14,15,39,41,42] -and decreased in individuals with higher educational attainment, possibly reflecting more efficient compensatory strategies in response to neuronal senescence [20]. This latter suggestion could be explored further through exploring structural and functional neuroimaging changes and their association with cognitive dispersion to better understand the influence of cognitive or brain reserve on variability in older age.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Overall, older drivers compensate for slower RTs and general cognitive decline in their driving behaviour [91]. However, recent findings have shown that protective factors against cognitive decline in older age, such as level of education and engagement, no longer facilitate compensation later in older age, when the cognitive reserve available to compensate is no longer sufficient for the demand for compensation, caused by declines in underlying cognitive resources [102,103]. The development of an assessment and training intervention that aims to assess and improve the ability to switch between tasks during driving, such as attending to traffic and reading road signs, could therefore be beneficial to the ageing population.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-individual variability may arise either from consistent differences between individuals (i.e., 'individuality' (Beauchamp, 2001;Eccard et al, 2020;Gosling, 2001; Gosling and John, 1999;Hasenjager et al, 2020;Honegger and de Bivort, 2018;Massol and Crochet, 2008;Nettle, 2006;Réale et al, 2007;Sih et al, 2004;Verbeek et al, 1994;Wolf et al, 2007)), and/or by individuals generally behaving inconsistently over time (i.e., 'spontaneity'; (Brembs, 2011;De Felice and Holland, 2018;Lichtenstein et al, 2017;Maye et al, 2007;Morgan and Neuringer, 1990;Jensen, 2013, 2010)). Of course, individuals may also differ consistently in their variability (Hertel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%